Identification Of The Characteristics Of Park Visitors To Nostalgia Urban Park, Kupang City, East Nusa Tenggara Province - Justhisia, Rinalice Izza; Yahya, Wisely; Simangunsong, Nur Intan (Universitas Trisakti, 2023)
Urban green spaces or open spaces play a critical role in sustaining urban natural environments and the social systems that use these spaces. Park accessibility is identified as one of the major factors in influencing park utilization. This study aim to identify the accessibility of Kupang Nostalgia Park. Data were collected through questionnaires from 100 park visitors. This study used a descriptive statistics through crosstabs analysis. There are a relationship in the relationship between the radius of residence of park visitors and the mode selection, as well as the relationship between the mode selection variable and the frequency of visits to the park. However, there is no correlation between the distance from visitor settlements and the frequency of visits to Nostalgia Park. Most of the visitors used private vehicles to access the Nostlagia Park. This study emphasizes that the supporting facilities that increase the accessibility need to be facilitated to increase the park visitors.